(untitled) (Research, Society and Development, 2022)
The energy use of non-renewable sources has encountered great difficulties due to increased costs and decreased availability of fossil fuels, in this sense, the use of winds as an energy source has gradually grown, becoming one of the main world energy matrices. Thus, this research is a quantitative and qualitative review focused on identifying the potential of wind energy as a renewable source, where, for such action, information and reports from government sources or renowned institutions and companies were filtered, in addition to of articles published in journals or proceedings of national congresses, books by recognized authors/publishers. Regarding the analysis of the data obtained, she indicated that within the alternative energies, wind is one of the most prosperous when analyzed at a global level, moreover, at a national level, in Brazil there are already 52 wind farms installed in the country, which make up a generation of 1,298.6 MW of power. Thus, it was possible to observe in this review that wind energy emerges as a "lifeline arrow" where the target is the energy propagation in a more sustainable way, especially in coastal areas and places with good availability in terms of wind dispersion.